STUDI EKSPERIMENTAL VARIASI SARINGAN UDARA KARBURATOR TERHADAP KINERJA MESIN SEPEDA MOTOR - Syaifullah, Syaifullah; Rubiono, Gatut; Bunawi, Bunawi (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2016)
Carburator air filter is an important part in automotive fuel system. Air filter is technicallymodified to increase the performance. This research is aimed to get the effect of air filter type due to motorcycle engine performance. The research is done by experiment using Suzuki Shogun 110 cc motorcycle. Air filter is vary as no filter, standard filter and modified filter. The engine is running at 1000, 2000, 3000 and 4000 rpm. The rotations are measured with tachometer. Time of fuel consumption is measured for 10 ml gasoline. Experiments are conducted 3 times. The data is use to get fuel consumption and engine efficiency. The research shows that carburator air filter has effect due to engine performance. Modified filter has better performance than standard filter and no filter.